Spondylothoracic dysostosis, Jarcho Levin syndrome: case report - Medina de la Cruz, Antonia Yesenia; Rodríguez Balderrama, Isaías; Burciaga Flores, Carlos Horacio; Martínez de Villarreal, Laura Elia; Ibarra Ramírez, Marisol; O Cavazos, Manuel Enrique de la (UANL. Facultad de Medicina, 2016)
Dysostosis spondylothoracic, or Jarcho Levin syndrome, is characterized by a short neck and thorax, a protruding abdomen, abnormal vertebral segmentation and fusion posterior costal resulting in thoracic restriction or respiratory failure and scoliosis. The prevalence is estimated at 1 in 12,000 live births for the people of Puerto Rico and 1 per 200,000 for the rest of the world. It is inherited in an autosomal recessive manner and the only related gene is MESP2. Clinical case: Newborn male, who during the first hour of life develops perioral cyanosis, thoracoabdominal dissociation and polipnea, requiring endotracheal intubation and mechanical ventilation for respiratory impairment, finding thoracoabdominal costovertebral abnormalities with an x-ray, and a conditioning restrictive pattern like a crab. During the physical examination, we found horizontal eyelid openings, right atrial appendage, straight nasal bridge, short thorax and asymmetry and hypertrichosis, predominantly in the back. A diagnosis of dysostosis spondylothoracic is confirmed, and the patient was discharged at 7 days of age, with follow up neonatal consultation at high risk.